A new method for calculating the direction of fracture propagation by stress numerical search based on the displacement discontinuity method. (December 2021) - Cong, Ziyuan; Li, Yuwei; Liu, Yu; Xiao, Yonghui
Abstract: In the traditional, displacement discontinuity method (DDM) simulation of hydraulic fracturing, the stress intensity factor (SIF) method is usually employed to calculate the fracture propagation angle (FPA). However, the SIF method is not suitable for real formation rock stress conditions. Considering the real stress condition of the formation under far-field bidirectional compression, we proposed a stress numerical search method (SNSM) that is based on the maximum circumferential stress criterion at the fracture tip to predict the FPA. Moreover, we compared the results from this model with indoor experiments and numerical simulation results to verify the model. The computation results of the model show that the traditional SIF method simplifies the rock stress, which will cause a large error and that the SNSM method is more consistent with the real situation. The sensitivity parameter analysis shows that the SNSM method can be utilized to predict the fracture propagation trajectory with different rock and construction parameters and to simulate the competitive growth of multiple fractures with the effect of a "stress shadow". The results of this paper supplement and improve the existing hydraulic fracturing model and can provide guidance for the fracture parameter design of field fracturing construction.